HAIBIO: Development of an e-magazine to Improve Biological Literacy - Ana Syafrotul Karomah; Evita Nury Hariyanti; Risda Putri Indriani; Rizhal Hendi Ristanto; Mieke Miarsyah (Journal of Science Learning, 2023)
The purpose of this research is to develop the learning media, i.e., a digital magazine, to improve the biological literacy skills of the students. The research method used Research and Development (RD) with ADDIE develops models. The developed learning media, HAIBIO, consists of biofact, bio lab, bioword, and biogame. The instrument test of biological literacy consists of 30 multiple-choice items based on four stages of biological literacy: nominal, functional, structural, and multidimensional. The validity test is conducted by paying attention to presentation, content, and language by two expert validators who say that media is valid to use in the class. The test of empirical validity is conducted for 30 students in class XI Science 1 in MAN 1 Bogor City. The empirical validity test results show that learning media are valid, and the instrument test found that 15 items are valid and five items are not. The reliability test result shows that 88% of respondents said that the instrument of biological literacy is reliable. The result of the normality test shows a significance value of 0,117 in α = 0.05, indicating that the data is normally distributed. The T-dependent test result shows a significance value of -7.679 with a t-table of -2.042 in α = 0.05. It shows that there is a higher enhancement score post-test than pre-test. The result of the N-Gain test is 0,44 in the medium category, and the effect size score is 2.93. That shows that HAIBIO e-magz is improving the biological literacy skills of the students.